PERBEDAAN VARIASI WAKTU KONTAK SINAR UV-C TERHADAP JUMLAH ANGKA TOTAL KUMAN PADA ALAT MAKAN - Qurrotul Aini Nur Mulya; Dindin Wahyudin; Bambang Yulianto (Politeknik Kesehatan Kemenkes Bandung, 2021)
Cutlery is one of the factors that play a role in disease transmission, because eating utensils that are not clean and contain microorganisms can transmit disease through food. regarding for the Total Plate Number on cutlery according to Permenkes RI Number 1096/MENKES/PER/VI/2011 about Jasaboga Sanitation,namely 0 colonies/cm2 of cutlery surface. This study aims to determine the difference in the contact time of UV-C rays on the number of total bacterial plates on cutlery plates. The sampling technique used is Simple Random Sampling. The results of the examination after being given a contact time of 15 minutes by UV-C light the average number of bacteria is 221 colonies/cm2 of the surface of the cutlery and for a contact time of 20 minutes the average number of bacteria is 102 colonies/cm2 of the surface of the cutlery and for a contact time of 25 minutes the average number of bacteria is 15 colonies/cm2 on the surface of the cutlery. Statistical test using one way ANOVA with the results of 0.000 <0.05, it can be concluded that there is a difference in the contact time of UV-C rays on the results of the Total Bacterial Plate Number on cutlery. It is necessary to re-do research related to the contact time of UV-C rays with a longer contact time.